Stress-Related Amygdala Metabolic Activity Is Associated With Low Bone Mineral Density in Postmenopausal Women: A Pilot 18F-FDG PET/CT Study - Pahk, Kisoo; Kwon, Hyun Woo; Joung, Chanmin; Kim, Sungeun (Frontiers in Endocrinology, 2021)
Background: Psychological stress is associated with postmenopausal osteoporosis. However, the underlying mechanism of stress-related brain neural activity with osteoporosis is not fully elucidated. 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) is an established method to evaluate the metabolic activity of brain amygdala, a region involved in stress. We aimed to evaluate the relationship between metabolic activity of amygdala (AmygA) and osteoporosis in postmenopausal women. Materials and Methods: A total of 115 postmenopausal women who underwent 18F-FDG PET/CT and dual-energy X-ray absorptiometry for routine health screening were enrolled in this study. AmygA was defined as the maximum standardized uptake value (SUVmax) of amygdala divided by the mean SUV of temporal lobe. The levels of psychological stress were measured using the Psychosocial Well-being Index-Short Form (PWI-SF). Results: The participants with osteoporosis exhibited significantly higher AmygA than without osteoporosis (0.81 ± 0.16 vs. 0.61 ± 0.13, p < 0.001). The AmygA value of 0.69 was suggested as an optimal cut-off value to identify participant with osteoporosis (sensitivity; 79.1%, specificity; 83.3%, area under the curve; 0.841, p < 0.001). Furthermore, AmygA showed significant association with osteoporosis in postmenopausal woman by multivariate analysis. Psychological stress scale (PWI-SF) was well correlated with AmygA and AmygA was highest in high stress risk-, intermediate in moderate stress risk-, and lowest in healthy group. Conclusions: AmygA measured by 18F-FDG PET/CT is associated with osteoporosis in postmenopausal women. Our results provide the possibility that stress-related neurobiological activity involving amygdala is linked with postmenopausal osteoporosis.